2017
DOI: 10.1002/macp.201700197
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Thermal, and Electrical Properties of Flexible Polythiophene with Disiloxane Side Chains

Abstract: Poly(3‐hexylthiophene) (P3HT) is widely shown to have considerable advantages in photovoltaic cells, including excellent electrical performance, but its fragility remains a challenge for material applications and processing of stretchable devices. Herein, high‐molecular‐weight and highly regioregular poly(3‐substituted thiophene) with disiloxane moieties in the side chains (P3SiT) is synthesized. An investigation of the molecular structure and physical properties of self‐supported cast films of P3SiT reveals e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 33 publications
(42 reference statements)
0
35
0
Order By: Relevance
“…Two remarkable peaks were observed at 2θ = 3.94° and 12.18°, respectively, as shown in Figure 2a. The result suggested that the thin film of the alternating copolymer 6c had a bilayer lamellar structure with 7.3 Å and 22.4 Å distances, respectively (Figure 2b) [13,29,30]. Molecular modeling of the alternating copolymer 6c suggested chain lengths of 11.6 Å and 2.2 Å, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Two remarkable peaks were observed at 2θ = 3.94° and 12.18°, respectively, as shown in Figure 2a. The result suggested that the thin film of the alternating copolymer 6c had a bilayer lamellar structure with 7.3 Å and 22.4 Å distances, respectively (Figure 2b) [13,29,30]. Molecular modeling of the alternating copolymer 6c suggested chain lengths of 11.6 Å and 2.2 Å, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Mori and coworkers reported the synthesis of regioregular polythiophene derivatives having soft siloxane units in the side chains . Indeed, the films of siloxane‐containing polythiophenes showed 2 orders of magnitude smaller Young's modulus and 20 times higher elongation at break than P3HT.…”
Section: Introductionmentioning
confidence: 99%
“…Mori and coworkers reported the synthesis of regioregular polythiophene derivatives having soft siloxane units in the side chains. [21][22][23] Indeed, the films of siloxane-containing polythiophenes showed 2 orders of magnitude smaller Young's modulus and 20 times higher elongation at break than P3HT. Previously, we also synthesized a regioregular polythiophene derivative with a trisiloxane group in the side chains via a hexamethylene spacer (P3SiHT) as shown in Figure 1.…”
mentioning
confidence: 99%
“…Two remarkable peaks were observed in 2θ = 3.94° and 12.18°, respectively, as shown in Fig 2 (a). The result suggests that the thin film of the alternating copolymer 6c shows bilayer lamellar structure involving 7.3 Å and 22.4 Å distances, respectively, 13,29,30 (Fig 2(b)) The molecular modeling of the alternating copolymer 6c suggests the chain lengths of 11.6 Å and 2.2 Å, respectively. The values of the observed layer distances of copolymer 6c closely corresponds to the twice values 11.6 x 2 and 2.2 x 2 (Fig 2(c) In summary, we have shown that formal alternating thiophene−thiophene copolymers were synthesized when a differently-substituted halobithiophene was employed as a monomer by nickel-catalyzed deprotonative polymerization was applied.…”
mentioning
confidence: 95%